Probe diagnostics of 63UFHe plasma, generated in the core of nuclear reactor WWW–K (International Journal of Mathematics and Physics, 2015)
In the present paper experimental results of probe measurements in nuclear induced plasma in the presence of negative ions are presented and used to define the ratio of electrons and negative ions di-rectly taken from electrostatic probe volt–ampere characteristic (VAC) inserted in the mixture. The nuclear induced plasma in the core of nuclear reactor was created by the following nuclear reaction